Digital Design for Finger Prosthesis Template: A Case Report - Gabriela Lintang Cristandy; Flavia Vonny Fransisca; Nina Ariani (Dentika: Dental Journal, 2025)
Prosthodontics is characterized by the incorporation of digital technology, which has transformed maxillofacial rehabilitation, providing quicker, more precise, and patient-friendly options. Therefore, this case report aimed to describe an alternative to traditional wax-up methods during the fabrication of a finger prosthesis using a digital workflow. Computer-aided design and manufacturing technology was a critical component in the rehabilitation of a 36-year-old male patient who suffered a loss of the right index finger due to trauma. Using an intraoral scanner, a digital scan of the afflicted area and the contralateral finger was acquired. To create the template design, the contralateral finger was mirrored and digitally sculpted using Autodesk Meshmixer software. A Phrozen LCD resin 3D printer was adopted to manufacture the finished design after being processed by nesting software. The template obtained was tried for anatomical accuracy, fit, and compatibility with the residual stump. The results showed that the method provided acceptable aesthetics and clinical fit while minimizing the number of patient visits. Integration of digital technology into the design was essential for achieving superior outcomes in finger prosthesis fabrication, which improved reproducibility, time efficiency, and patient comfort. In conclusion, the method proposed may serve as a realistic option in prosthetic rehabilitation, particularly for partial finger defects